Gender-biased behavior at work: what can surveys tell us about the link between sexual harassment and gender discrimination? - Heather Antecol; Vanessa E. Barcus; Deborah A. Cobb-Clark (Institute for the Study of Labor (IZA), 2007)
This paper examines the links between survey-based reports of sexual harassment and gender discrimination. In particular, we are interested in assessing whether these concepts measure similar forms of gender-biased behavior and whether they have the same effect on workers' job satisfaction and intentions to leave their jobs. Our results provide little support for the notion that survey-based measures of sexual harassment and gender discrimination capture the same underlying behavior. Respondents do appear to differentiate between incidents of sexual harassment and incidents of gender discrimination in the workplace. Both gender discrimination and sexual harassment are associated with a substantially higher degree of job dissatisfaction, particularly amongst men. While women who experience gender discrimination are somewhat more likely to intend to change jobs, amongst men it is sexual harassment that leads to an increased propensity to quit. We find no significant interactions between our two measures of gender bias, perhaps implying that the intensity of gender bias is relatively unimportant for understanding job dissatisfaction and the intention to quit. At the same time, this may reflect the lack of precision with which we estimate this interaction, especially for men
urn:nbn:de:101:1-20080416151
Keywords: 330; Sexuelle Belästigung; Geschlechterdiskriminierung; Arbeitszufriedenheit; Arbeitsmobilität; Männliche Arbeitskräfte; Frauenerwerbstätigkeit; USA